The militarization of public schools and the developments in childhood and youth (Research, Society and Development, 2022)
The research aims to analyze the consequences in childhood and adolescence of the militarization of public schools. This is an integrative literature review carried out through the Google Scholar, SCORPUS, Web of Science databases using the keywords: “militarization”, “adolescent” and “public school”. Combined with each other by the Boolean AND operator. As inclusion criteria: articles available in full, in Portuguese, Spanish and English, that addressed the theme, in the last ten years (2012-2022). As exclusion criteria: articles that did not contemplate the theme and repeated studies in the databases. The model of the school's military administration with the general performance of the national army companies dates back to 1998; however, the change from public schools in the interior, which were in operation, to the management of the PM is a phenomenon that began in Goiás, in 1998, when the authorities of the government of Marconi Perillo created and installed a school for the navy, supported by a 1976 law , to provide differentiated schooling for dependents of the navy. It is essential to highlight that, just as the phenomenon of militarization is recent and blunt in sentences of punishment for public schools, the manufacture of know-how about this university mannequin has received prominence and is developing in Brazilian universities.